1992
DOI: 10.1111/j.1752-0606.1992.tb00948.x
|View full text |Cite
|
Sign up to set email alerts
|

Treating Adolescent Drug Abuse: A Comparison of Family Systems Therapy, Group Therapy, and Family Drug Education

Abstract: The differential effectiveness of three models of adolescent drug abuse treatment was assessed in a controlled outcome study. Family Systems Therapy (FST) was compared to Adolescent Group Therapy (AGT) and Family drug Educations (FDE). FST appeared to be more effective in stopping adolescent drug abuse than AGT or FDE, registering twice as many apparently drug‐free clients than FDE and three times as many as AGT. However, a number of possible confounds make this conclusion tentative. No tretment approach was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(93 citation statements)
references
References 8 publications
2
91
0
Order By: Relevance
“…Similarly, treatment completion rates for youths in therapeutic communities have ranged from 10% to 18%, with approximately one-third of the youths leaving treatment within the first month (Pompi, 1994). Reported peer group treatment dropout rates have been as high as 49% (Liddle & Dakof, 1995) and 56% (Joanning, Quinn, Thomas, & Mullen, 1992). Ogborne (1995) reported that 33% (194 cases) of those aged 12 to 25 who presented to eight outpatient programs for substance abuse treatment dropped out before their assessment was completed.…”
mentioning
confidence: 99%
“…Similarly, treatment completion rates for youths in therapeutic communities have ranged from 10% to 18%, with approximately one-third of the youths leaving treatment within the first month (Pompi, 1994). Reported peer group treatment dropout rates have been as high as 49% (Liddle & Dakof, 1995) and 56% (Joanning, Quinn, Thomas, & Mullen, 1992). Ogborne (1995) reported that 33% (194 cases) of those aged 12 to 25 who presented to eight outpatient programs for substance abuse treatment dropped out before their assessment was completed.…”
mentioning
confidence: 99%
“…Many studies document high treatment drop out rates among substance abusing adolescents (3)(4)(5)(6). These early drop-out rates are most often associated with a lack of motivation for change (2) and comorbid diagnosis (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the involvement of families in the treatment of drug-addicted children is viewed as essential by international bodies such as the American Academy of Child and Adolescent Psychiatry [11]. A number of studies have demonstrated the superiority of family therapy approaches over other treatments when dealing with child and adolescent drug users [12,13]. Consequently, services in Dublin dealing with increasing numbers of children have had to create new treatment programs for this age group, developing new skills to meet the rapidly evolving problem [6].…”
Section: Discussionmentioning
confidence: 99%